Volatility of the USD: Effects from economic policy uncertainty, monetary policy uncertainty and geopolitical risk - Thaw, Jia Yee (2023)
In recent years, there has been an increase in economic uncertainties, with uneven growth seen in various economies leading to a divergence of monetary policies of major economies. Furthermore, geopolitical events like instability in politics, wars, and natural disasters can affect the value of the US currency, leading to volatility in the USD. This uncertainty can affect trade and consumption patterns due to the unpredictable nature of the exchange rate movements. Thus, this study aims to examine the relationship between economic policy uncertainty index (EPU), monetary policy uncertainty index (MPU), and geopolitical risk index (GPR) on the volatility of the USD. Using data from 342 months from January 1994 to June 2022 in the United States, this study employs the Generalized Autoregressive Conditional Heteroskedasticity (GARCH) to analyze the data. The main findings indicate that only EPU and MPU are significant in affecting the volatility of the USD. EPU has a positive and significant impact, while MPU has a negative and significant impact on the volatility of USD. The finding that the GPR is not significant in explaining the volatility of USD suggests that geopolitical events and risks do not play a major role in driving US exchange rate volatility. The results of this study suggest that the US government can take various steps to reduce EPU, including increasing the transparency and predictability of economic policy. Additionally, the study indicates that monetary policy uncertainties are less concerning for businesses, consumers, investors, and policymakers. However, companies involved in international trade and investment face currency risks, which arise from the fluctuation in exchange rates. Therefore, they should consider using hedging strategies to manage their currency risks effectively. Overall, this study contributes to the understanding of the complex and uncertain dynamics of the volatility of USD, which can help policymakers and businesses make better decisions to manage their risks and improve the stability of global financial system.